PEMANFAATAN APLIKASI GOOGLE EARTH DALAM PEMBELAJARAN SEJARAH DI SMA NEGERI 4 KOTA JAMBI - Nikmah, Khoirun; Pamungkas, Satriyo (Universitas Batanghari Jambi, 2022)
The purpose of this study was to determine student responses to the application of the Google Earth application in history learning at SMK Negeri 4 Jambi City. The research that will be conducted is a descriptive quantitative research type because the researcher describes it based on the data that has been collected as it is. Based on the results of research that has been carried out regarding the use of the google earth application in history learning at SMA Negeri 4 Jambi City in class X 4. Based on the data from the student questionnaire as many as 35 people consisting of three indicators, namely indicators of interest, indicators of activity, and indicators of courage. In the interest indicator, an average percentage of 78.06% is included in the